Hemangiolymphangioma of the cervical region: A rare case report (Indian Journal of Case Reports, 2026)
Hemangiolymphangioma is a rare developmental anomaly. Vascular anomalies are classified under two categories, including vascular tumors and vascular malformations, based on cellular turnover, histology, and clinical features. Hemangioma is an example of a vascular tumor, and lymphangioma is an example of a vascular anomaly. Malformations can be seen in mixed combinations of vascular elements, such as blood and lymph. Histologically, vessels filled with both blood and lymph are named as lymphangiohemangioma or hemangiolymphangioma, depending on the dominant tissue present. This paper reports a case of hemangiolymphangioma in a 20-year-old male patient.